A Review of Research on the Bioactivity of Stevia Rebaudiana Sp. (Phenolic and Flavonoid Compound Content and DPPH) in Morocco, Mexico, and Indonesia - Johana Fitriani; Deni Rahmat (Eduvest - Journal of Universal Studies, 2026)
Stevia rebaudiana is a plant that contains many compounds with high antioxidant potential, but differences in activity are influenced by solvent factors and the growing environment. For this reason, this article review collects data on the types of solvents and the parts of the plant that can be used as the best sources for antioxidant activity. The method used in this literature review article (LRA) involves collecting and analyzing various journals that discuss the phytochemical and antioxidant activities of Stevia rebaudiana. Results from studies on the ethanol extract of S. rebaudiana leaves in Mexico show that the total phenolic content (TPC) in both Criolla and Morita varieties is lower than the total flavonoid content (TFC), while in Morocco, the TPC content is higher than the TFC. Based on DPPH test results, ethanol is the best solvent for extracting Moroccan Stevia, and the most suitable part of the plant to use is the leaves. The antioxidant activity varies across different regions. Furthermore, analysis of S. rebaudiana chromatogram varieties using HCA and PCA multivariate analysis can reveal the dominant marker and active compounds of the Stevia plant in each region.